Identify And Remove Time And Location Dependent Attack Using Trust Concept for MANETs - Kumari, Namrata; Agrawal, Chetan; Meena, Pooja (International Journal of Computer Sciences and Engineering, 2025)
One of the sort of ad-hoc network is Mobile ad hoc networks (MANETs). MANETs are making them arrange and owned formulated network and there is no concentrated base station. In routing forwarding the data packet between nodes is core issue due to badly behaving or untrustworthy nodes present in the network. Recommendation trust model is a framework to find out the untrustworthy nodes and provide routes for packets to destination. A trust demonstrate takes recommendation by nodes transforms into an issue in light of the nearness of deceptive proposition like as ballot-stuffing, bad-mouthing and collusion. Untrustworthy nodes in the existing trust models lead to attacks by using recommendation which is investigated in this paper. Time and Location Dependent Attack Detection (TLDAD) Approach has been proposed in this paper to successfully sift through attacks identified as dishonest recommendation. The fundamental commitment of this work is to identify and remove time and location dependent attack related to recommendation Trust Model in MANETs. The model is tested under a couple of mobile and isolated topologies within which nodes find some changes in neighborhood provoking regular course changes. This paper focuses on a secure communication path across the nodes in the network. The experimental examination shows activeness and accuracy of the proposed method in a dynamic MANET condition.